(untitled) (Research, Society and Development, 2020)
Football is a high level sport, very popular and one of the main forms of leisure for a large part of the world population. In addition to having an increasing number of practitioners, this sport has undergone many changes in recent years, mainly due to the increasing physical demands of athletes, forcing them to work close to their limits and leaving them prone to suffering injuries that can cause losses to athletes In this context, this study aimed to identify the most frequent injuries in professional soccer athletes, point out the most affected field position, demonstrate the importance of sports physiotherapy in injury prevention programs and highlight techniques and methods used in these programs. This is a literature review study, in which the content of the subject was analyzed. The search for scientific information available in the literature occurred in the electronic databases Scielo, Google Acadêmico and Pubmed. Articles investigating the importance of sports physical therapy in injury prevention programs for professional players, published between 2002 and 2017, in Portuguese and English were investigated. The most frequent injuries in professional football are muscle stretching, bruising, swelling, contracture, ankle sprain and rupture. Planning an injury prevention program with professional football players can be considered an excellent method for reducing casualties in the health department of clubs.